Oxygen uptake kinetics and energy system`s contribution around maximal lactate steady state swimming intensity - Pelarigo, J. G.; Machado, L.; Fernandes, R. J.; Coelho Greco, C.; Vilas-Boas, J. P. (PLOS ONE, 2017)
The purpose of this study was to examine the oxygen uptake () kinetics and the energy systems` contribution at 97.5, 100 and 102.5% of the maximal lactate steady state (MLSS) swimming intensity. Ten elite female swimmers performed three-to-five 30 min submaximal constant swimming bouts at imposed paces for the determination of the swimming velocity (v) at 100%MLSS based on a 7 x 200 m intermittent incremental protocol until voluntary exhaustion to find the v associated at the individual anaerobic threshold. kinetics (cardiodynamic, primary and slow component phases) and the aerobic and anaerobic energy contributions were assessed during the continuous exercises, which the former was studied for the beginning and second phase of exercise. Subjects showed similar time delay (TD) (mean = 11.5-14.3 s) and time constant (tp) (mean = 13.8-16.3 s) as a function of v, but reduced amplitude of the primary component for 97.5% (35.7 ± 7.3 mL.kg.min-1) compared to 100 and 102.5%MLSS (41.0 ± 7.0 and 41.3 ± 5.4 mL.kg.min-1, respectively), and tp decreased (mean = 9.6-10.8 s) during the second phase of exercise. Despite the slow component did not occur for all swimmers at all swim intensities, when observed it tended to increase as a function of v. Moreover, the total energy contribution was almost exclusively aerobic (98-99%) at 97.5, 100 and 102.5%MLSS. We suggest that well-trained endurance swimmers with a fast TD and tp values may be able to adjust faster the physiological requirements to minimize the amplitude of the slow component appearance, parameter associated with the fatigue delay and increase in exhaustion time during performance, however, these fast adjustments were not able to control the progressive fatigue occurred slightly above MLSS, and most of swimmers reached exhaustion before 30min swam.